Characterization of tuberculous lesions in naturally infected African buffalo (Syncerus caffer) - Laisse, Claudio Joao Mourao (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSc (Biomedical Sciences. Medical Biochemistry))--University of Stellenbosch, 2010.